2020
DOI: 10.3390/f12010027
|View full text |Cite
|
Sign up to set email alerts
|

The Reproductive Strategy as an Important Trait for the Distribution of Lower-Trunk Epiphytic Lichens in Old-Growth vs. Non-Old Growth Forests

Abstract: (1) Research Highlights: The work studied the beta diversity patterns of epiphytic lichens as a function of their reproductive strategies in old-growth and non-old growth forests from the Mediterranean area. (2) Background and Objectives: The reproductive strategies of lichens can drive the dispersal and distribution of species assemblages in forest ecosystems. To further investigate this issue, we analyzed data on epiphytic lichen diversity collected from old-growth and non-old growth forest sites (36 plots) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Allen & Lendemer (2016) emphasized the vulnerability of high-elevation lichens to climate change, highlighting a trend also observed in our study, where rare lichen species exhibit significant sensitivity to changing moisture regimes. Similarly, Brunialti et al (2021) and Fazan et al (2022) explored the reproductive strategies of epiphytic lichens, providing a context for understanding how aridification might affect lichen reproduction and, consequently, their long-term survival and distribution. Honegger (2022) and Khastini et al (2019) provided foundational knowledge on lichen biology and ecology, reinforcing the importance of studying lichen as indicators of environmental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allen & Lendemer (2016) emphasized the vulnerability of high-elevation lichens to climate change, highlighting a trend also observed in our study, where rare lichen species exhibit significant sensitivity to changing moisture regimes. Similarly, Brunialti et al (2021) and Fazan et al (2022) explored the reproductive strategies of epiphytic lichens, providing a context for understanding how aridification might affect lichen reproduction and, consequently, their long-term survival and distribution. Honegger (2022) and Khastini et al (2019) provided foundational knowledge on lichen biology and ecology, reinforcing the importance of studying lichen as indicators of environmental health.…”
Section: Discussionmentioning
confidence: 99%
“…This focus is not only driven by the need to understand their ecological role but also to use their responses to forecast environmental changes, including those induced by climate change. The loss of lichen diversity is increasingly being recognized as an indicator of broader ecological shifts, prompting a need for comprehensive studies in diverse geographical regions (Brunialti et al, 2021;Steinová et al, 2022;Lukashchuk et al, 2023). Such research is critical for developing conservation strategies and understanding the dynamic interplay between lichens and their environments on a global scale.…”
Section: Introductionmentioning
confidence: 99%
“…Lobaria pulmonaria usually inhabits old-growth forests, which is why it is perceived as an indicator of forest ecological continuity (e.g., Brunialti et al, 2015b;Whittet & Ellis, 2013), which reacts negatively to changes in the stand structure caused by forest management and human activity (Di Nuzzo et al, 2022;Edman et al, 2008;Jüriado & Liira, 2010;Otálora et al, 2011). e sensitivity of this species and its high ecological requirements make it a good indicator of key habitats for relic and rare epiphytic lichens in autochthonous or ancient forests (Brunialti et al, 2015a;Motiejūnaitė et al, 2004;Nilsson et al, 1995;Paoli et al, 2019).…”
Section: 2mentioning
confidence: 99%
“…On comparing logged and unlogged stands in Mediterranean oak forests, Bianchi et al [15] pinpointed a lower growth of the threatened lichen Lobaria pulmonaria in the logged stands than in the unlogged ones. They suggested that effective conservation-oriented management for this species should be tailored the Still considering lichens, Brunialti et al [16] hypothesized that the dispersal abilities to the different reproductive strategies drive the species' beta diversity depending on forest age and continuity. They showed that sexually reproducing lichen species have high turnover, while vegetative species tend to form nested assemblages, especially in old-growth forests with respect to non-old-growth ones.…”
mentioning
confidence: 99%